PERAN MONUMEN TIROSA TERHADAP PENINGKATAN PENDAPATAN UMKM - Alfonzo Rodrigues Watudesi; Afrandi Sugiardi Gandur; Benediktus Maurisko Geong; Herodias Ardi Pranto; Yohanes Pemandi Lian (JURNAL ADMINISTRASI KANTOR, 2024)
This article discusses the role of the TIROSA Monument in enhancing the income of Micro, Small, and Medium Enterprises (MSMEs) in KUPANG City, East Nusa Tenggara. Located in the city center, the monument serves as a strategic tourist attraction. The research employs a qualitative approach with a descriptive method, involving interviews and observations. The results indicate that while the TIROSA Monument has significant potential, challenges such as inadequate supporting facilities and cleanliness affect visitors’ interest. Recommendations are provided to improve facilities and foster collaboration among the government, community, and MSME actors to optimize tourism potential. Keywords: TIROSA Monument, MSMEs, Tourism, Income, Facilities